The Phenomenon of Divorce is Caused by Online Gambling in East Jakarta - Aziz, Abdul (Al-madinah: Journal of Islamic Civilization, 2024)
The phenomenon of divorce due to online gambling in East Jakarta has become a worrying issue, with a significant increase in recent years. This study aims to identify the factors that lead to the rise in online gambling-related divorce rates and develop effective strategies for recovery. The research method involves collecting data through surveys, in-depth interviews with affected families, and analyzing Islamic legal literature regarding online gambling. The results of the study showed that online gambling addiction causes serious damage to family structures, including severe financial problems, mental health disorders, and erosion of trust between family members. The study also found that ease of access and economic incentives are the main reasons people engage in online gambling. The impact of these findings underscores the need for comprehensive interventions, such as public education on gambling risks, emotional and financial support for affected families, and affordable rehabilitation programs. This study concludes that recovery strategies that involve collaboration between governments, health institutions, and local communities are urgently needed to reduce the negative impact of online gambling and help families get back on a healthier track. Proactive and collaborative efforts can effectively address this problem and reduce the divorce rate related to online gambling in East Jakarta.